Karakteristik Sosial-Ekonomi dan Tingkat Kepuasan Penghuni terhadap Rumah Bersubsidi di Kecamatan Ungaran Timur - Nonik Astomukti; Asnawi Asnawi (Jurusan Perencanaan Wilayah dan Kota, 2020)
House is one of basic needs for human as a shelter for living and doing activities. However, many houses are overpriced so that not everyone can afford it. As a solution to the overprized housing, the government provides subsidized housing program for the low-income society. The satisfaction level of residents is considered as the main factor for government and developer to assess the program. The aim of this research is to find out the socio-economic characteristics and the satisfaction level of subsidized housing residents in the sub-district of East Ungaran. This research is using descriptive statistic, GAP and IPA analysis with 71 residents as the sample. Variables for this research are (1) the physical condition of the house, (2) the condition of the infrastructure, facilities, and utility of the residential environment, (3) the location of the residential, (4) the status of ownership, (5) the conveniency and the security of the environment (liveability) and (6) the social environment. The results of this study are the level value shows that the highest level of residents’ satisfaction with subsidized housing is the social environmental aspect with a Gap value of 0.17, a good social environment with active social activities and good relationship with neighbours. The government and developer can make the results of the IPA diagram quadrant as a consideration for further development of subsidized housing.